Pengaruh Dosis Pupuk Kandang Sapi Terhadap Pertumbuhan Dan Hasil Tanaman Jagung Manis (Zea mays Saccharata Sturt.) Varietas Paragon F1 - Siska Auliani; Pandu Sumarna; Fadhillah Laila; Yudhi Mahmud; Fina Dwimartina (Jurnal Agro Wiralodra, 2026)
Hybrid sweet corn is of high quality that is able to adapt in a variety of environments. For optimal crop yields, effective nutrient management is needed, including the provision of cow manure that has a high fiber content in appropriate and sustainable doses. The purpose of this study was to determine the effect of cow manure dosage on the growth and yield of the best Paragon F1 variety sweet corn plants. The research was carried out on rice fields in Pekandangan Village, Indramayu District, in July – September 2024. The experimental design used in this study was a Group Random Design (RAK) consisting of 5 treatments that were repeated 5 times each . The 5 cow manure dose treatments are S0 = control, S1 = 15 tons/ha, S2= 25 tons/ha, S3 = 35 tons/ha, S4 = 45 tons/ha. The results showed that there was an effect of the use of cow manure on all components of growth and yield of sweet corn plants at the best dose of 25 tons/ha, with a yield of 2.20 tons/ha.